Opportunities of Strategic Alliances: Malaysian Perspectives - Abdul Ghani, Ahmad Bashawir; Mahyudin, Emil; Kaewsoman, Chumphon; Boonmuang, Sathid (Medwell Journal, 2016)
With the emergence of stiff competition there has been an increased focus on the use of inter-firm relationships or strategic alliances in delivering best service packages to the consumer. Despite a number of studies there is still much to be learned about why alliances form and why they take the form they do. Based upon case based methodology in Malaysia this research argues that the formation of strategic alliances is due to firms seeking out new market opportunities under conditions of increased uncertainty and competition. We adopt resource dependence views of alliance formation with those of conventional economics and argue that alliances are a means of reducing the uncertainty that surrounds the undertaking of new market opportunities.